Aetiology of acute gastroenteritis in infancy and early childhood in southern India. Issue 6 (June 1977) - Maiya, P P; Pereira, S M; Mathan, M; Bhat, P; Albert, M J; Baker, S J
Abstract : The aetiology of acute gastroenteritis was studied in 50 infants and young children. Bacterial pathogens were isolated in 33, enteropathogenic E. coli (EPEC), Salmonella, and Shigella being the commonest isolates. Rotaviruses were detected in the stools of 13 of the cases. All children with gastroenteritis in whom rotavirus was detected were seen during the months July to December. In 30 children who served as controls, EPEC were isolated in 6, but rotavirus was detected in none. It is concluded that infection with rotaviruses is a significant cause of morbidity in children with gastroenteritis in southern India.